2008
DOI: 10.1099/jmm.0.47237-0
|View full text |Cite
|
Sign up to set email alerts
|

Is lipopolysaccharide a factor in infectivity of Chlamydia trachomatis?

Abstract: Lipopolysaccharide (LPS) is a major surface component of Chlamydia trachomatis, as with all Gram-negative bacteria. The effect of C. trachomatis LPS on C. trachomatis infectivity of human epithelial cells was investigated. C. trachomatis LPS and C. trachomatis LPS antibody significantly reduced infectivity, mostly in a dose-dependent manner. As the structure of LPS in C. trachomatis is simple and consists only of lipid A and 3-deoxy-D-manno-octulosonic acid (Kdo), we investigated whether lipid A or Kdo was inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…The idea of differential requirements for infectivity between serovars and various species of Chlamydia is well accepted, especially for the specific ligand-receptor interactions during bacterial attachment and entry (27). In support of our findings, it has been reported that C. trachomatis serovar E was more susceptible to various LOS inhibitors than serovar LGV in vitro (19). Clearly, it will be critical to evaluate the efficacy of DS-96, and further developed chemical analogs, using clinically relevant serovars of Chlamydia in animal challenge studies.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…The idea of differential requirements for infectivity between serovars and various species of Chlamydia is well accepted, especially for the specific ligand-receptor interactions during bacterial attachment and entry (27). In support of our findings, it has been reported that C. trachomatis serovar E was more susceptible to various LOS inhibitors than serovar LGV in vitro (19). Clearly, it will be critical to evaluate the efficacy of DS-96, and further developed chemical analogs, using clinically relevant serovars of Chlamydia in animal challenge studies.…”
Section: Discussionsupporting
confidence: 81%
“…Fadel and Eley postulated a general role of LOS in Chlamydia infectivity (19). They demonstrated that infection of human epithelial cells by C. trachomatis serovar LGV and serovar E was inhibited in the presence of purified LOS, PMB, antibody against C. trachomatis LOS, and synthetic Kdo (19).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations